The development of fraud prevention policies in the public sector: A bibliometric analysis - Mabel, Serah Novarida; Payamta, Payamta; Winarna, Jaka (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2025)
Fraud in the public sector has become a global issue that impacts national finances, institutional integrity, and public trust. This study aims to analyze fraud prevention strategies in the public sector through a bibliometric approach based on 61 Scopus-indexed articles published between 2015 and 2024. The methodology employed is bibliometric analysis with the help of VOSviewer software to identify research trends, influential authors, and key topics related to fraud prevention. The findings suggest that new technologies such as artificial intelligence (AI), blockchain, and data analytics play a crucial role in enhancing transparency and detecting fraud more effectively. Furthermore, an ethical organizational culture, strong leadership commitment, and robust internal control systems are important factors in mitigating fraud risks. This study concludes that an approach combining cutting-edge technology and strong governance is necessary for sustainable fraud prevention in the public sector.